Long-term results of treatment in multidrug-resistant mycobacterium tuberculosis patients interrupting a chemotherapy cycle - A. I. Gaida; E. I. Nikishova; A. O. Maryandyshev (Туберкулез и болезни лёгких)
The long-term results of treatment were studied in multidrug-resistant tuberculosis (MDR-TB) patients who had interrupted a chemotherapy cycle in the civil sector of the Arkhangelsk Region. In January 2005 to December 2009, interrupted treatment for MDR-TB was registered in 211 patients. All the patients were divided into 4 groups: 1) 74 patients who had taken less than 100 doses of antituberculosis drugs; 2) 64 patients who had received 100 to 200 doses; 3) 34 patients who had 200 to 300 doses; 4) 39 patients who had more than 300 but less than 720 doses. A comparative analysis of the long-term results of treatment in MDR-TB patients who had interrupted treatment showed that the percentage of clinical resolution increased and tuberculosis death rates decreased in relation to the number of taken drug doses. The clinical resolution rate in the patients who had interrupted treatment for MDR-TB and received more than 300 but less than 720 doses (for more than 10 months) was ascertained to be high and equal to 79.5%. In the patients who had completed a treatment cycle for MDR-TB, the latter recurred in 5.2% of cases on average during a 2-year follow-up. A repeated chemotherapy cycle was recorded in 10.2% of the patients who had been treated for more than 10 months and who had interrupted a chemotherapy course. Further investigations are needed to decide whether MDR-TB chemotherapy cycle should be reduced to 10-12 months.